Scale of Professional Identity of Physical Education Teachers: Development and validation procedures - José António Marques Moreira; António Gomes Ferreira; Joaquim Armando Ferreira (Desafio Singular, 2014)
This paper reports the procedures to design a physical education teachers' professional identity scale and its psychometric features. After reflecting on the construct and its operationalisation, we analyzed the procedures required for its design and validity of the construct (factorial analysis) and analyzed the internal consistency by calculating the Cronbach alpha coefficient. After carrying out a pre-test and then administering a scale to a sample of 206 physical education teachers, we concluded that the instrument has satisfactory psychometric qualities. The analysis of the internal consistency of the two factors identified showed that the instrument is reliable. Thus, because these factors are internally consistent and well defined by the items, we concluded that the scale has psychometric qualities that support its use as a reliable research instrument. Further to providing good validity indicators, the measures applied are characterized by being reliable or adequately reliable and having interpretable factorial structures, suggesting that they consistently assess the variables they intend to measure, thus being an appropriate instrument to assess the professional identity of physical education teachers.